The impact of salt-tolerant plants on soil nutrients and microbial communities in soda saline-alkali lands of the Songnen plain - Song, Junjie; Guan, Xueting; Cui, Haojun; Liu, Lin; Li, Yan; Li, Yuhua; Ma, Shurong (Frontiers in Microbiology, 2025)
IntroductionSoil salinization poses a significant threat to agricultural development and ecosystem health. While phytoremediation is an effective approach, the mechanisms by which salt-tolerant plants mediate saline-alkali soil amelioration in the Songnen Plain remain unclear.MethodsWe selected seven common salt-tolerant plants from the Songnen Plain to compare soil nutrients and microbial communities between vegetated areas and bare alkali patches. Soil salinity, pH, nutrient content (TN, TP, TK), enzyme activities (Catalase, Cellulase, Saccharase, Urease), and microbial structure were analyzed.ResultsPlant presence significantly reduced soil salinity and pH while increasing nutrient levels and enzyme activities, with SL (Salix linearistipularis) showing the most comprehensive improvement. Vegetation enhanced microbial abundance/diversity (bacteria and fungi), with EC (R2 = 0.7308, P = 0.0001) and TN (R2 = 0.5706, P = 0.0001) as key drivers of diversity changes. Microbial composition shifted markedly: beneficial phyla (e.g., Mortierellomycota, Acidobacteriota) increased, while pathogenic Chytridiomycota decreased. Community variations were primarily influenced by EC (R2 = 0.8778, P = 0.001) and pH (R2 = 0.8661, P = 0.001). Plants also promoted functional groups involved in carbon/nitrogen cycling.DiscussionThese findings demonstrate that salt-tolerant plants enhance soil fertility and restructure microbial communities in saline-alkali soils, with EC/pH and TN as critical regulatory factors. This study provides a scientific basis for sustainable saline land rehabilitation via targeted vegetation restoration.